Managing Deep Sea Tailings Placement And The Environment: An Analogue For Deep Sea Mining - Tracy Shimmield (International Marine Minerals Society, 2011)
Deep sea tailings placement (DSTP) techniques have been pioneered in Papua New Guinea (PNG): a mining reliant economy in a seismically active region, facing major environmental challenges in the safe handling and storage of mine tailings on land. Scientists at SAMS have researched impacts of DSTP on the marine environment specifically to inform and develop guidelines for the use of DSTP to reduce environmental impact, thereby lowering risk and increasing private sector investment. Guidelines have been established as regulation by the PNG Government providing reassurance to private investors, facilitating an increase in mining exports to 60% of total export. Researchers investigated the effects of DSTP at 2 PNG mines: Lihir Gold Mine which has been actively discharging tailings since 1996 and Misima Mine, closed in 2004 after discharging tailings for 15 years, allowing an assessment of the recovery of the marine environment after tailings placement. Research involved investigating ocean currents and mixing, the behaviour of metals and the effect of tailings on benthic communities including the risk of elevated metal contents entering the food chain. The research established a metal ?fingerprint? of tailings compared to natural sediments, which enabled the transport of fine tailings within the deep ocean to be ascertained.